Analysis Criteria for Regional Resilience in Areas Affected by Disasters - Herrera-Enríquez, Giovanni (2018)
The main objective of this research is to define resilience within the parameters of complex adaptive systems and to understand its dynamics within heuristic model of panarchy to evaluate the characteristics of the regional systems that could be affected by natural disasters. The analytical methods and variables identified are systemized and evaluated considering the reality of the territories located in developing countries where information is deficient or non-existent. Resilience is considered multidimensional, so that eight dimensions of analysis can be identified. We propose 56 study criteria that were obtained from various cases and opinions of experts from Ecuador and Chile.